Handbook of Ancient Afro-Eurasian Economies : : Volume 1: Contexts - Dwivedi, Mamta; Fabian, Lara; Leese-Messing, Kathrin; Morris, Lauren; Weaverdyck, Eli J. S. (2020)
Abstract: The Handbook of Afro-Eurasian Economies offers the first comprehensive discussion of economic development in the empires of the Afro-Eurasian world region to elucidate the conditions under which large quantities of goods and people moved across continents and between empires. Volume 1: Contexts provides succinct histories of the most important parts of the Afro-Eurasian landmass during a period of dynamic empire building (300 BCE to 300 CE), surveys the most important evidence and methods for understanding their economic histories, and introduces readers to the different traditions of scholarship that have shaped contemporary research on economic development across this region